2011
DOI: 10.1007/s12237-011-9421-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Effects of Wastewater Effluent on Growth, Survival, and Accumulation of Microbial Contaminants by Oysters in Mobile Bay, Alabama

Abstract: We measured seasonal effects of wastewater treatment plant (WTP) effluent on growth, survival, and accumulation of microbes in oysters near a major WTP in Mobile Bay, AL. Despite higher nutrients near the WTP, seasonal conditions rather than distance affected chlorophyll a concentration and oyster growth. In summer and fall, when oyster growth was higher, δ 15 N‰ in oysters near the WTP changed through time to reflect δ 15 N‰ in effluent (approx. −4‰). Microbial indicators (male-specific coliphage, fecal colif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Al though some of the environmental attributes measured during this study differed significantly between the 2 study sites, this variation was not significant enough to cause differences in oyster growth be tween sites. Values for water temperature, salinity, and DO were typical of summer conditions in the study area (Stumpf et al 1993, Cowan et al 1996, Park et al 2007 and consistent with suitable oyster growth conditions in Mobile Bay (Biancani et al 2012). Water-column chl a values were within the range reported in previous studies (Cowan et al 1996, Biancani et al 2012, and SPM and POM concentrations were similar to or higher than those reported for suitable oyster growth elsewhere (Grizzle et al 1992, Ferreira et al 1997, Carmichael et al 2012b.…”
Section: Factors Affecting N-removal Capacitysupporting
confidence: 84%
“…Al though some of the environmental attributes measured during this study differed significantly between the 2 study sites, this variation was not significant enough to cause differences in oyster growth be tween sites. Values for water temperature, salinity, and DO were typical of summer conditions in the study area (Stumpf et al 1993, Cowan et al 1996, Park et al 2007 and consistent with suitable oyster growth conditions in Mobile Bay (Biancani et al 2012). Water-column chl a values were within the range reported in previous studies (Cowan et al 1996, Biancani et al 2012, and SPM and POM concentrations were similar to or higher than those reported for suitable oyster growth elsewhere (Grizzle et al 1992, Ferreira et al 1997, Carmichael et al 2012b.…”
Section: Factors Affecting N-removal Capacitysupporting
confidence: 84%
“…Because the detection of all waterborne potential faecal pathogens is very sensitive, various indicators of faecal contamination are usually used to detect faecal pollutions in natural waters [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Bivalve molluscan shellfish feed on algae from the surrounding water. During this feeding process, each bivalve mollusc may filter 20 to 90 liters of water per day and bioaccumulate a variety of microorganisms, including viruses and bacteria that are associated with pollution sources (8,(10)(11)(12). Significantly, molluscan shellfish have been found to retain viruses to a greater extent and for much longer periods than they do bacteria (8,13,14).…”
mentioning
confidence: 99%